Pengendalian Kontaminasi Total Coliform pada Depot Air Minum Isi Ulang dengan Konsep Hazard Analysis Critical Control Point - Rinda Andhita Regia; Taufiq Ihsan; Dhita Dwi Tirta (Universitas Andalas, 2020)
Total Coliform as an indicator of food or beverage pollution can cause food-borne diseases. In the food and beverage production process, hygiene and sanitation are part of the Hazard Analysis Critical Control Point (HACCP) is one of the efforts to avoid pollution to the production process. This study aims to control Total Coliform contamination with the HACCP concept carried out in 10 drinking water depot in Pauh Subdistrict, Padang City through direct field observation and laboratory testing using the Most Probable Number (MPN) method. The test point in this study is the raw water contained in the reservoir, the production water that will be sold to consumers and the drinking water will be consumed for 3 days in gallon. The test results showed hygiene and sanitation of drinking water depot and Total Coliform content had a negative and strong relationship (r = -0.750) means that the higher the hygiene and sanitation of drinking water depot, so the lower the Total Coliform content in drinking water. Based on the results of the hazard analysis which is the CCP point are the filter tube, UV light and gallon washing. Therefore, control measures so that the CCP point that exceeds the quality standard can be accepted are controlling the drinking water process and tightening hygiene and sanitation of drinking water depot employees. Keywords: Total Coliform, Drinking Water Depot , HACCP, Pauh Sub-dDistrict, hygiene sanitation ABSTRAK Total Coliform sebagai indikator pencemaran makanan atau minuman dapat menyebabkan penyakit bawaan makanan. Dalam proses produksi makanan dan minuman, kebersihan dan sanitasi yang menjadi bagian dari Hazard Analysis Critical Control Point (HACCP) adalah salah satu upaya untuk menghindari polusi pada proses produksi. Penelitian ini bertujuan untuk mengendalikan kontaminasi Total Coliform dengan konsep HACCP yang dilakukan di 10 depot air minum (DAMIU) di Kecamatan Pauh, Kota Padang melalui observasi lapangan langsung dan pengujian laboratorium menggunakan metode Most Probable Number (MPN). Titik uji dalam penelitian ini adalah air baku yang terkandung dalam reservoir, air produksi yang akan dijual kepada konsumen dan air minum akan dikonsumsi selama 3 hari dalam galon. Hasil tes menunjukkan kebersihan dan sanitasi depot air minum dan kandungan Total Coliform memiliki hubungan negatif dan kuat (r = -0,750) berarti semakin tinggi kebersihan dan sanitasi DAMIU, sehingga semakin rendah kandungan Total Coliform dalam air minum . Berdasarkan hasil analisis bahaya, yang merupakan titik CCP adalah tabung filter, sinar UV dan pencucian galon. Oleh karena itu, langkah-langkah pengendalian terhadap poin kritis yang menyebabkan tidak tercapainya standar kualitas, adalah dengan mengendalikan proses air minum dan memperketat kebersihan dan sanitasi karyawan DAMIU. Kata kunci: Total Coliform, DAMIU, HACCP, Kecamatan Pauh, sanitasi perorangan